Integrated Adolescent Health Promotion Through Mental Health Monitoring, Anemia Prevention, And Digital Reproductive Health Education in Rejomulyo Village - Aprin Rusmawati; Dhita Kurnia Sari; Prima Dewi Kusumawati; Alfian Fawzi (Journal of Community Engagement in Health, 2026)
Adolescents face various health challenges related to mental health, anemia, and reproductive health due to rapid biological, psychological, and social changes. Limited health literacy and exposure to unverified digital information increase the risk of unhealthy behaviors. This community engagement program aimed to improve adolescents’ knowledge, awareness, and preventive behavior through integrated health education interventions. The program combined mental health education using daily mood check cards and breathing relaxation techniques, anemia screening and education, and digital-based reproductive health education (MODEKSI DIGITAL). Activities were conducted in Rejomulyo Village involving adolescents through counseling sessions, interactive discussions, screening activities, and digital learning media. Evaluation methods included observation of participation, discussions, and assessment of knowledge improvement before and after the intervention. Results indicated increased emotional awareness, improved understanding of anemia prevention and balanced nutrition, and enhanced knowledge of reproductive health and responsible digital media use. Participants demonstrated high engagement and positive responses toward the educational activities. Challenges included inconsistent participation and limited emotional literacy among some participants. The integrated community-based approach proved effective in strengthening promotive and preventive health behavior among adolescents. Continuous mentoring and sustainable health education programs are recommended to maintain long-term impact.